Modern physics : for scientists and engineers - Morrison, John C., 1940-; ScienceDirect eBooks (London : Academic, 2010)
Intended for a first course in modern physics, following an introductory course in physics with calculus, Modern Physics for Scientists and Engineers begins with a brief and focused account of the historical events leading to the formulation of modern quantum theory, while later chapters delve into the underlying physics. Streamlined content, chapters on semiconductors, Dirac Equation and Quantum Field Theory, and a robust pedagogy and ancillary package including an accompanying website with computer applets assists students in learning the essential material. Ancillary list: * Online ISM- http://textbooks.elsevier.com/web/manuals.aspx?isbn=9780123751126 * Online SSM- http://booksite.academicpress.com/Morrison/physics/sm.php * Companion website- http://booksite.academicpress.com/Morrison/physics/ * Applets http://booksite.academicpress.com/Morrison/physics/applets.php Develops modern quantum mechanical ideas systematically and uses these ideas consistently throughout the book Carefully considers fundamental subjects such as transition probabilities, crystal structure, reciprocal lattices, and Bloch theorem which are fundamental to any treatment of lasers and semiconductor devices Uses applets which make it possible to consider real physical systems such as many-electron atoms and semi-conductor devices.
This work begins with a brief account of the historical events leading to the formulation of modern quantum theory, while later chapters delve into the underlying physics. It includes sections on semiconductors, quantum field theory, transition probabilities and Bloch theorem to assist readers in learning the essential material.
The Wave-Particle Duality The Schrodinger Wave Equation Operators and Waves Hydrogen Aton Many-Electron Atoms The Emergence of Masers and Lasers Statistical Physics Electronic Structure of Solids Charge Carriers in Semiconductors Semiconductor Lasers Relativity I Relativity II Particles Physics Nuclear Physics Appendix A: Natural Constants and Conversion Constants Appendix B: Table of Atomic Masses Appendix C: Solution of the Oscillator Equation Appendix D: The Average Value of the Momentum Appendix E: The Hartree-Fock Applet Appendix F: Integrals that Arise in Statistical Physics Appendix G: The ABINIT Applet.
Title from title screen (viewed on Apr. 4, 2012).
Includes bibliographical references and index.
Elsevier
Keywords: Physics; Physics; Electronic books; Electronic books